Startup Project Leadership dalam Meningkatkan Produktivitas Pembelajaran di Masa Pandemi - Wahyuddin Wahyuddin; Herlyana Herlyana; Habriani Habriani; Rahmawati Rahmawati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Learning problems amid a pandemic tend to be one-way. Teachers provide more one-way information and assignments to students without feedback, resulting in boredom for students studying online. Therefore, one solution is given through the startup project leadership (SPL) program. This activity was held on October 31 - November 27, 2020, at three elementary schools: SDN Mangkura III Makassar, SDN 234 Barambang II Maros Regency, and SD IT Asshiddiq Bone Regency, involving as many as 40 students. The results of the activity can be concluded that the SPL Program is a collaborative action of teachers in innovating to create quality education in the pandemic era consisting of 3 stages: Incubation which is the initial planning carried out by designing joint activities with students and parents related to the problems faced by students and solutions that will be applied; Startup which is an active activity for program realization agreed at the incubation stage; and Mobilization which is the final stage through process reflection, evaluation, and conclusion drawing, as well as follow-up to the results of program realization that have been carried out. The implementation of SPL is running well according to the time and targets that have been determined and can increase learning productivity during pandemics.